1991
DOI: 10.3168/jds.s0022-0302(91)78635-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of Interferons in the Control of Infectious Diseases of Cattle

Abstract: Recovery from infection involves a number of complex interactions between specific cells of the immune system. Many of these interactions are mediated by cytokines, which can activate these cells to kill or reduce the replication rate of the pathogen. Availability of large quantities of recombinant cytokines has provided the opportunity to investigate the mechanism or mechanisms of action of each cytokine in vitro and in vivo. In the present review, we describe the application of interferons to reduce morbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…As a remarkable small molecule that participates in immune responses, interferon-gamma (IFN-γ) is widely used for infection resistance and clinical treatment [10]. For mastitis, IFN-γ could reduce the level of infection caused by different pathogenic bacteria, it also has immunotherapeutic value in the control of bovine mastitis [11]. In Staphylococcus infection, IFN-γ is generated from the capsular polysaccharide simulated T cells and obviously boosts the injurious effects of resistant staphylococcus [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a remarkable small molecule that participates in immune responses, interferon-gamma (IFN-γ) is widely used for infection resistance and clinical treatment [10]. For mastitis, IFN-γ could reduce the level of infection caused by different pathogenic bacteria, it also has immunotherapeutic value in the control of bovine mastitis [11]. In Staphylococcus infection, IFN-γ is generated from the capsular polysaccharide simulated T cells and obviously boosts the injurious effects of resistant staphylococcus [9].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines have clinical potential, especially in conventional therapy for persistent infectious diseases [10]. Interferon (IFN) in particular has been reported to induce antiviral activities against many viruses in vitro, and is used for medical treatments against persistent virus infections in humans and experimentally in animals [1,2,16]. Recently, recombinant DNA techniques have made it possible to produce IFN on a large scale, which will help make it economically feasible to bring that cytokine into general use for the control of many infectious animal diseases.…”
Section: Animalsmentioning
confidence: 99%
“…However, the time of peak concentration in this study of 24 h for mice differed from 6 h in cows infected with lipopolysaccharide ( Vels et al, 2009 ). It has been reported that the concentration of serum TNF-α is closely associated with acute signs and contributes to morbidity and mortality For coliform mastitis ( Babiuk et al, 1991 ; Sordillo and Peel, 1992 ). TNF-α plays an essential role in immunity response by inducing plasma haptoglobin, recruiting and activating neutrophils, and elevating intramammary and systemic nitrite and nitrate ( Blum et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%